2024
DOI: 10.1109/jphot.2023.3347709
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Microwave Photonic Mixer With High Spurs Suppression and Image Rejection

Gai Shen,
Yue Zhou

Abstract: Abstract-A microwave photonic mixer for up-and downconversion based on dual parallel in-phase and quadrature (I/Q) modulators is proposed. Dual parallel I/Q modulators and 90degree electrical hybrid couplers are used to obtain carriersuppressed single-sideband modulation of radio frequency (RF), intermediate frequency (IF), and local oscillator (LO) signals.The optical bandpass filter (OBPF) is employed to select the -1storder or +1st-order sideband of the LO signal to realize up and down conversion. In the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…It can be observed that the IF signal generated by the image signal frequency conversion is well suppressed with an IRR of 51.35 dB as presented in Figure 11a. In the same situation without using a 90 • optical hybrid coupler, the IRR is also better than the 45.91 dB in [10]. Additionally, in Figure 11b, the amplitude of the IF signal waveform generated by the frequency conversion of the image signal is almost zero.…”
Section: Image Rejection and Sfdrmentioning
confidence: 82%
See 3 more Smart Citations
“…It can be observed that the IF signal generated by the image signal frequency conversion is well suppressed with an IRR of 51.35 dB as presented in Figure 11a. In the same situation without using a 90 • optical hybrid coupler, the IRR is also better than the 45.91 dB in [10]. Additionally, in Figure 11b, the amplitude of the IF signal waveform generated by the frequency conversion of the image signal is almost zero.…”
Section: Image Rejection and Sfdrmentioning
confidence: 82%
“…For example, Zhu et al proposed a frequency down-conversion scheme based on CS-SSB modulation via an integrated DP-MZM [19]. Shen and Zhou proposed a dual parallel in-an I/Q modulators-based microwave photonic mixer [10]. Considering frequency conversion efficiency, the above-mentioned solutions have their limitations since they can only achieve down-conversion of a single frequency and are only suitable for point-to-point scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations